Implementasi Augmented Reality Sebagai Media Interaktif Edukasi Anak Untuk Peningkatan Kognitif - Hidayani, Nur; Rosyidah, Ulya Anisatur; Abdurrahman, Ginanjar (Puslitbang Akademi Relawan TIK Indonesia, 2024)
In the world of education, especially in kindergarten education, there is a problem with the use of technology, namely excessive dependence on gadgets. The solution provided for this problem is Augmented Reality-based learning using the markerbased method. This application provides an innovative and interactive experience through 2-dimensional and 3-dimensional displays as well as visual and audio displays. The research method used a literature study involving lecturers from the Faculty of Teacher Training and Education in order to validate a questionnaire for usability testing which was specifically conceptualized for the purpose of increasing cognitive understanding in kindergarten children. The research results showed that the educational interactive media application for kindergarten children with the aim of increasing cognitive understanding in the HICIHAA application showed an increase of 17.09% in the aspect of cognitive understanding.